2022
DOI: 10.1002/ejic.202200374
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of a Diatomic Acceptor Ligand: A Reliable Measure of Its Antibond Occupation and Its Charge?

Abstract: A nitrosyl ligand is bonded to a central metal mainly via a mostly covalent normal bond and a coordinative metal‐to‐NO π‐backbond. A recent analysis had unravelled similar bonding characteristics of both linear and bent CoNO moieties in terms of ligand charge and antibond occupation. Thus, there should be no justification for the usual assignment of an NO+ ligand to a linear MNO unit and a singlet‐NO− ligand to a bent one. This claim seems to contradict that bending an MNO unit weakens the N−O bond with a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
0
8
0
2
Order By: Relevance
“…, the two-atomic system NO, which then should be true, independent of the system in which the NO is integrated. This can be clearly seen when inserting the calculated decoupled values from the study of Popp & Kluefers 28 for different metal-nitrosyl complexes, as shown in Fig. 7.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…, the two-atomic system NO, which then should be true, independent of the system in which the NO is integrated. This can be clearly seen when inserting the calculated decoupled values from the study of Popp & Kluefers 28 for different metal-nitrosyl complexes, as shown in Fig. 7.…”
Section: Discussionmentioning
confidence: 74%
“…26 Fundamental insight into these questions and, especially, also with respect to the oxidation state of the ''non-innocent'' ligand NO, has been given in the recent work by Klu ¨fers and co-workers. 27,28 Through detailed structure analysis combined with DFT calculations and the determination of the charges on the NO, it was shown that the M-N-O angle is not a reliable indicator to derive bond strengths or ligand charges.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the GS/MS transition of 1 is a non‐DCD event which lacks the DCD‐typical charge/bond‐strength correlation of an acceptor ligand. The physical origin of the observed redshift, lateral electrostatic influence on bending, is addressed in a separate work [22] …”
Section: Resultsmentioning
confidence: 99%
“…schen Ursache der beobachteten Rotverschiebung, nämlich lateraler elektrostatischer Einfluss bei der Abwinkelung, wird in einer eigenen Arbeit adressiert. [22] Der TS lohnt eine nähere Betrachtung. Entgegen der üblichen Zuordnung der Ladungen in linearen und gewinkelten MNO-Funktionen ändern sich im Verlauf des linear/gewinkelt-Übergangs in 1 die Ladungen der Nitrosylliganden nicht signifikant.…”
Section: Methodsunclassified
“…Es wird deutlich, dass die GS/MS‐Umwandlung in 1 kein DCD‐Ereignis ist und daher der DCD‐typischen Ladungs–Bindungsstärke‐Beziehung die Grundlage fehlt. Die physikalischen Ursache der beobachteten Rotverschiebung, nämlich lateraler elektrostatischer Einfluss bei der Abwinkelung, wird in einer eigenen Arbeit adressiert [22] …”
Section: Ergebnisse Und Diskussionunclassified